Analisis Kompensasi, Lingkungan Dan Disiplin Kerja Pada Kinerja Karyawan PT Multindo Auto Finance Jawa Timur Di Area XV - Nadia Pita Sari; Imam Baehaki (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This study aims to analyze the effect of compensation, environment and work discipline on employee performance. Employee performance that is needed by every company to make a company grow efficiently. Data collection was carried out through questionnaires and carried out on 44 employees of PT Multindo Auto Finance East Java in Area XV. Data analysis in this study uses SPSS version 20. The results of the analysis show: (1) That compensation has a significant effect on employee performance, (2) the environment has a significant effect on employee performance. Work Discipline has a significant effect on employee performance. (4) Compensation, environment, and work discipline together have a significant effect on employee performance. (5) The most dominant compensation variables that affect employee performance.